A schoolwide enrichment program: Case study of Maktab Rendah Sains MARA Taiping as a special school for the academically gifted - Abdul Rahman, Azly; Mohamad, Mutiara (Universiti Utara Malaysia, 1995)
The paper of this brief paper is to describe the contents of an ethnographic survey (July 1994-1995) on the nature of programming of a secondary school designated for the academically gifted. This paper will describe Maktab Rendah Sains Mara MARA Taiping's (MRSM Taiping) programme for school wide enrichment beyond the curriculum guidelines given by the Ministry of Education. The discussions will begin with a brief history of gifted and talented programming (G/T programming)in general; from the time of plato to the current advancements in neuro-scientific principles of learning, and move on to provide information on Majlis Amanah Rakyat's (MARA)effort in educating the academically superior. Next, we shall describe the philosophy, mission, vision and the strategies (macro, micro and neuro) employed by Maktab Rendah Sains MARA Taiping in its effort to carve a niche as MARA's foremost secondary educational institution for the "academically gifted". Lastly, included in this survey description is a MRSM Taiping teacher professional develop "in-house-training" course description which illustrate the current efforts being made to align the schools curriculum and instructional development with that of the latest research especially in the United States. Principally, the researchers found out that MRSM Taiping has a clear vision in its G/T programming guided by Joseph Renzulli's Triad Model of Enrichment consisting of three stages called Type I (exploration of content), Type II (developing of higher order thinking skills) and Type III (group investigations on research problem). It was also found out that in general, teachers of the G/T program have a clear understanding of the goals of the MRSM Taiping G/T program. This paper will finally conclude with recommendations on the areas of research needed to bridge the knowledge gap of Malaysian G/T education; an area which still needs "acceptance" as an avenue for democratizing mass education.